Anthropomorphic Measurements of the Arm Span and Their Correlation with the Stature of Bengali Adult Muslim Females (Medicine Today, 2012)
Medicine Today 2009 Volume 21 Number 02 Page 70-71 DOI: http://dx.doi.org/10.3329/medtoday.v21i2.12550